Diving deeper into seep distribution along the Cascadia convergent margin, United States - Rudebusch, Jane A.; Prouty, Nancy G.; Conrad, James E.; Watt, Janet T.; Kluesner, Jared W.; Hill, Jenna C.; Miller, Nathaniel C.; Watson, Sally J.; Hillman, Jess I. T. (Frontiers in Earth Science, 2023)
Previous margin-wide studies of methane seep distribution along the Cascadia Subduction Zone indicate peaks in seep density within the landward limit of the of gas hydrate stability zone (GHSZ; ≤500 m depth), suggesting a link between current ocean warming, acceleration of hydrate dissociated, and methane emissions. This inferred connection, however, may not account for regional geologic and/or structural complexities driving methane seepage. Expanding upon an existing seep database by adding new seeps data, we conducted statistical and spatial analyses to determine margin-wide distribution trends and offer a tectonic framework for understanding the tendency toward non-normality and spatial clustering. We then highlight the role of local-scale drivers of seep formation in addition to the first-order tectonic framework, using systematic geologic/geomorphic characterization of seep emission sites in southern Cascadia and case studies using meta-attribute analysis of seismic reflection data.. Seep distribution along the margin is non-random, but instead of clustering along the 500-m isobath, regions of high seep density occur in canyons and topographic highs. New findings from this study conclude that co-location of the outer arc high (OAH) and the landward limit of the GHSZ may explain high concentrations of seeps where deformation is the greatest and hydrates are unstable. Detailed analysis of the spatial relationships between seep sites and geologic-geomorphic features in southern Cascadia reveal a link between seeps and anticlines, with 52% of the seeps found in association with anticlines, 36% found at faults, 16% associated with canyons, and 11% at seafloor failure scarps. Given that a majority of anticlines are located along or seaward of the OAH in the actively deforming outer wedge, we suggest that the location of the OAH is a primary structural control on seep distribution. This scenario is supported by neural network analysis of multichannel seismic data revealing zones of probable fluid migration along vertical pipes, faults, and chimneys in the vicinity of active seep sites on anticlines. Determining linkages between seeps and submarine tectonic geomorphology is a crucial first step for understanding and forecasting the distribution of methane seepage, but also a necessity for evaluating causal relationships between ocean warming and gas-hydrate stability.